The Influence of English Teacher's Nonverbal Interaction on EFL Students' Perception of Learning - Nur Isnani (ELE Reviews: English Language Education Reviews, 2021)
English teachers have proximity control, which is described by walking closer to the noisy part of the class and continuing to be there until the commotion subsides. However, there are still some students who are indifferent during the learning process. Therefore, this research aims to determine the influence of English teacher's nonverbal interactions on EFL students' perception at State Islamic Senior High School 1 Bengkalis. This research is causal-comparative research. There are two instruments: observation and questionnaire. The population of this research is 208 students. Then, the researcher uses simple random sampling and chooses 40 students from all classes. Using simple linear regression analysis formula through SPSS 20.0 in analyzing the data, the researcher found that sig-t was 0.000, smaller than 0.05 (sig-t < 0.05). The result showed a significant influence of the English teacher’s nonverbal interactions on EFL students’ perception at State Islamic Senior High School 1 Bengkalis. It means that Ha was accepted. The researcher also found that the value of R square was 0.546, namely squaring of the Standardized Coefficients ((0.739 x 0.739)2 x 100% = 0.546). R square can be called the coefficient of determination, which means that the English teacher's nonverbal interaction influences 54.6% of EFL students' perception. Then, the other 45.4% is influenced by other factors.